(untitled) (Journal of Science and Technology, 2016)
This study was undertaken with the objective of evaluating the extent of convergence on the part of key stakeholders in the cocoa sector on the problems of cocoa extension and how to address it. The study was carried out in the Atwima Mponua and Amansie West districts of the Ashanti region in 2008 although some of the stakeholders interviewed were outside these districts. Survey research methodology was employed including focus group discussions to obtain information from policy makers, researchers, extensionists, licensed buying companies, input dealers and farmers. The key findings were that all concurred that productivity should be boosted to improve the lot of farmers and that information provision is central to this. However, there was no convergence as to how this could be achieved. It emerged that the state of cocoa extension was deplorable requiring urgent policy intervention. The implications and conclusions are that farmers are not benefitting sufficiently from many years of cocoa research; to move productivity to a higher pedestal, the acknowledged knowledge gap between researchers and farmers need to be bridged.